Elevated CO2 degassing rates prevented the return of Snowball Earth during the Phanerozoic - Benjamin J. W. Mills (Nature Portfolio, 2017)
Despite dramatic changes in carbon sinks, severe Snowball Earth glaciations have not occurred since the Cryogenian. Here, via the measurement of global subduction zone lengths and carbon cycle modelling, the authors show that a two fold increase in volcanic CO2 input likely thwarted global glaciation.